Genomic imbalances in syndromic congenital heart disease - Miriam Coelho Molck; Milena Simioni; Társis Paiva Vieira; Ilária Cristina Sgardioli; Fabíola Paoli Monteiro; Josiane Souza; Agnes Cristina Fett-Conte; Têmis Maria Félix; Isabella Lopes Monlléo; Vera Lúcia Gil- (Elsevier, 2017)
Objective: To identify pathogenic genomic imbalances in patients presenting congenital heart disease (CHD) with extra cardiac anomalies and exclusion of 22q11.2 deletion syndrome (22q11.2 DS). Methods: 78 patients negative for the 22q11.2 deletion, previously screened by fluorescence in situ hybridization (FISH) and/or multiplex ligation probe amplification (MLPA) were tested by chromosomal microarray analysis (CMA). Results: Clinically significant copy number variations (CNVs ≥300 kb) were identified in 10% (8/78) of cases. In addition, potentially relevant CNVs were detected in two cases (993 kb duplication in 15q21.1 and 706 kb duplication in 2p22.3). Genes inside the CNV regions found in this study, such as IRX4, BMPR1A, SORBS2, ID2, ROCK2, E2F6, GATA4, SOX7, SEMAD6D, FBN1, and LTPB1 are known to participate in cardiac development and could be candidate genes for CHD. Conclusion: These data showed that patients presenting CHD with extra cardiac anomalies and exclusion of 22q11.2 DS should be investigated by CMA. The present study emphasizes the possible role of CNVs in CHD. Resumo: Objetivo: Identificar desequilíbrios genômicos patogênicos em pacientes apresentando Cardiopatias Congênitas (CC) e anomalias extra cardíacas, e exclusão da Síndrome de Deleção 22q11.2 (SD22q11.2). Métodos: Um total de 78 pacientes negativos para a deleção 22q11.2, previamente testados por hibridação in situ com fluorescência (FISH) e/ou amplificação de múltiplas sondas dependentes de ligação (MLPA), foram avaliados por microarray cromossômico (CMA). Resultados: Foram identificadas variações do número de cópias de DNA (CNVs) clinicamente significativas (≥ 300 kb) em 10% (8/78) dos casos, além de CNVs potencialmente relevantes em dois casos (duplicação de 993 kb em 15q21.1 e duplicação de 706 kb em 2p22.3). Genes envolvidos como IRX4, BMPR1A, SORBS2, ID2, ROCK2, E2F6, GATA4, SOX7, SEMAD6D, FBN1 e LTPB1 são conhecidos por atuarem no desenvolvimento cardíaco e podem ser genes candidatos a CC. Conclusão: Estes dados mostram que pacientes apresentando CC, com anomalias extra cardíacas e exclusão da SD22q11.2, devem ser investigados por CMA. Ainda, este estudo enfatiza a possível função das CNVs nas CC. Keywords: DNA copy number variations, Congenital heart defects, 22q11 deletion syndrome, Comparative genomic hybridization, Chromosome aberrations, Palavras-chave: Variações do número de cópias de DNA, Cardiopatias congênitas, Síndrome de deleção 22q11, Hibridização genômica comparativa, Aberrações cromossômicas